The adaptability of informal institutions - Gruszewska, Ewa (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The study is guided by a set of research questions. How do informal institutions change? Does their deep historical and cultural embeddedness imply that such a change necessarily occurs at a slow pace? And to what extent can informal institutions be considered adaptive in responding to external pressures? Aim: The author’s primary intention was to investigate the specific character of informal institutions, with particular emphasis on their adaptive capacity. The analysis focuses on the factors that may trigger adaptation processes, and whether these changes can occur under certain conditions over a relatively short period of time. Results: The study finds that informal institutions, though typically slow to evolve, exhibit uneven persistence across different clusters of norms. Some categories respond more quickly to external pressures, such as the introduction of new formal rules, shifts in socio-economic conditions, or political upheavals. These responses may generate new practices that, once routinised, crystallise into new social norms. Such adaptive dynamics foster complementarities among institutional components, reinforcing systemic coherence and enhancing the stability of the broader institutional order.